Online Marketing Analysis for a Selected Company in Malaysia - Soeung, Hong (2022)
Importance of internet communication and online marketing has increasingly emerged as businesses can now connect, communicate, and maintain relationship with customers through various digital platforms namely websites, social media accounts and emailing. Since such communication methods are less direct but significantly more persuasive and attractive comparing to the traditional promotion techniques, online marketing has become a vital tool not only for existing gigantic businesses but also for those fresh startups as well. This diploma thesis aims to analyze the current online marketing of a selected anonymous company and propose recommendations to the company after obtaining key results from the analyses. It evaluates the effectiveness and efficiency of the digital tools implemented by the company. The study seeks to answer the question “How well has the company exploited the online marketing tools in their business?”. In order to answer this research question, it is necessary to discover theoretical foundations regarding Internet marketing and its disciplines. Analyses on the company’s website, social media channels and SEO position of the webpage are conducted to assess the company’s online profiles on social networks as well as the quality of its website in terms of technicality and website content.